Blood pressure changes following extracorporeal shock wave lithotripsy in Kirkuk province - Muhammadamin, Kamaran Y.; Alshawni, Muhammad A.; Darweesh, Omeed O. (Zanco Journal of Medical Sciences (ZJMS), 2012)
Background and Objectives: Hypertension has been reported as a possible sequela of extracorporeal shock wave lithotripsy, the aim to determine, in a clinical trial, the effect of extracorporeal shock wave lithotripsy (ESWL) on blood pressure. Methods: This study included 216 patients, aged (12-65) years, with asymptomatic renal stones that were undergo ESWL in lithotripter unit/ Azadi teaching hospital –Kirkuk Province. Blood pressure was recorded at randomly using a standardized protocol. Patients undergoing ESWL received a mean (±SD) of 3608.8 (±475.9) shocks over a mean (6.81) of sessions on one lithotripter. Patients were then followed-up assessing their blood pressure. Data were analyzed on an intention for the treatment basis. Results: At randomization (13.42) % of the study group was hypertensive. Of (320) patients referred to the study, (258) were recruited based on the inclusion and exclusion criteria. A total of (216) patients (83 % of patients included) completed follow up, (137) (63.42%) were male and (79) (36.57%) were female. The mean follow-up peiod was (15.03) months. In the present study there was no association between mean diastolic and systolic blood pressure before and after ESWL. Conclusions: In the present study which included a randomized controlled clinical trial there was no evidence that ESWL causes changes in BP. More randomized control trials are needed to demonstrate the relationship between ESWL and hypertension.